[PP.09.19] LONG-TERM WELL-CONTROLLED BLOOD PRESSURE LEVELS AND CAROTID ELASTICITY IN YOUNG HYPERTENSIVE SUBJECTS. (September 2017) - Puato, M.; Rattazzi, M.; Pesavento, R.; Fania, C.; Palatini, P.; Pauletto, P.
Abstract : Objective: Aim of the study was to evaluate the impact of long-term well-controlled blood pressure (BP) on local arterial stiffness in hypertensives. Arterial stiffness increases with age and this process can be exacerbated by the presence of cardiovascular risk factors such as hypertension. Carotid distensibility evaluation is a reliable method that could reflect the stiffness of arteries. Design and method: We studied 40 young hypertensives (mean age 49.7 years) that had been kept on pharmacological treatment and/or on lifestyle modification for at least 12 months (mean 38 months) to maintain target BP. Follow-up visit were scheduled every 6-month. Carotid compliance coefficient (CC) and distensibility coefficient (DC) were measured by B-mode based system coupled with dedicated software. We assessed mean carotid intima-media thickness (IMT) and maximum IMT in each carotid artery segment, bilaterally. Endothelial function was evaluated by post-occlusion flow mediated dilation (FMD). Forty normotensive subjects paired for age and sex served as controls. Results: In the hypertensives, BP levels were well controlled (office BP 131/79 mmHg). Compared to controls, significantly higher BP levels and BMI were present in hypertensives, whereas age and metabolic parameters were similar. Compared to normotensives, carotid elasticity was significantly impaired in hypertensives (DC 24.5 ± 8.9 vs 36.9 ± 8.5 10–3/kPa, and CC 0.92 ± 0.34 vs 1.28 ± 0.36 mm 2 /kPa). Local stiffness parameters were inversely related to age, BP, and LDL-cholesterol. Moreover, DC and CC were inversely related to IMT measurements and directly with FMD values. Conclusions: In hypertensives with long term well-controlled BP, it is evident an increase in arterial local stiffness respect normotensive controls.